Exercise Capacity in Unilateral Diaphragm Paralysis: The Effect of Obesity. (1st April 2019) - Richman, Paul S.; Yeung, Pomin; Bilfinger, Thomas V.; Yang, Jie; Stringer, William W.
Abstract : Purpose . Healthy patients with unilateral diaphragm paralysis (UDP) are often asymptomatic; those with UDP and comorbidities that increase work of breathing are often dyspneic. We report the effect of obesity on exercise capacity in UDP patients. Methods . All obese and nonobese patients with UDP undergoing cardiopulmonary exercise testing (CPET) during a 32-month period in the exercise laboratory of an academic hospital were compared to a retrospectively identified cohort of obese and nonobese controls without UDP, matched for key features. CPET used a modified Bruce treadmill protocol with breath-to-breath expired gas analysis. O2 uptake, minute ventilation, exercise time, and work rate were recorded at peak exercise. Static pulmonary functions were measured. Kruskal-Wallis, Wilcoxon rank sum, and Fisher's exact tests were used to compare continuous and categorical variables, respectively. Stratified linear regression was used to quantify the effect of UDP and obesity on CPET variables. Results . Twenty-two UDP patients and 46 controls were studied. The BMI of obese and nonobese patients was 33.0±4.2 and 25.8±2.4 kg/m2, respectively. UDP subjects with obesity, compared to controls with neither condition, showed significantly reduced peak O2 uptake normalized to actual body weight (1.57±0.64 versus 2.01±0.88 L/min), shorter exercise time (5.7±2.0 versus 8.5±2.9 minutes), and lower peak ventilation. This was not observed in UDP alone or obesity alone. Peak work rate trended lower in the combined UDP-obesity group. Conclusion . Neither UDP nor obesity alone significantly reduced exercise capacity. Superimposed UDP and obesity interact to create a ventilatory limitation to exercise, with reduced peak-VO2, exercise time, and work rate.